How do cardiovascular risk factors and cardiac remodeling type affect left ventricular global longitudinal strain and right ventricular free wall strain in patients with obesity. (3rd October 2022) - Mogollon, R; Quintero-Martinez, J; Vallejo, B; Garcia-Arango, M; Cordova-Madera, S; Pislaru, S; Kane, G; Villarraga, H
Abstract: Background: Obesity, defined by the World Health Organization (WHO) as a BMI greater than 30k g/m 2, has reached epidemic proportions worldwide, related to approximately 2.8 million deaths/year as of June 2021. WHO sub-classifies obesity based on BMI in Class 1: 30–34.9 kg/m 2, Class 2: 35–39.9 kg/m 2, and Class 3: ≥40 kg/m 2 . This state of increased body weight is associated with an increased risk of cardiovascular disease. Cardiac remodeling can be affected by obesity and/or other cardiovascular risk factors (CVRF) as an adaptive physiological response. The remodeling patterns, Normal Geometry (NG), Concentric Remodeling (CR), Concentric Hypertrophy (CH), and Eccentric Hypertrophy, are classified by changes in Relative Wall Thickness (RWT), ≤ or >0.42, and/or Left Ventricular Mass Index (LVMI g/m 2 ), ≤ or >88 for women and ≤ or >102 for men. Left Ventricular Ejection Fraction (LVEF) can remain within normal limits in patients with obesity with multiple CVRF and cardiac remodeling. Left Ventricular Global Longitudinal Strain (LV-GLS) and Right ventricular free wall strain (RV-FWS) can be useful to detect subclinical myocardial dysfunction. The aim of this study was to evaluate if these strain variables are affected in patients with obesity associated to other CVRF in relation to cardiac remodeling type when compared to controls. Methods: 2859 patients with BMI ≥30 kg/m 2 and 2616 normal-weight controls (BMI between 18.5 and 24.9 kg/m 2 ), with normal and abnormal cardiac geometry, and normal ejection fraction by echocardiography performed between 01/01/2008 and 12/31/2018, were compared. Obesity was classified based on the World Health Organization. CVRF included were Hypertension (HTN), Diabetes Mellitus (DM), Dyslipidemia, history of Vascular Event (myocardial infarction and/or stroke), and Obstructive sleep apnea (OSA). Results: BMI, cardiac geometry, CVRF, and the number of comorbidities independently affected GLS and RV-FWS (Figure 1 and Figure 2). LV-GLS and RV-FWS values [mean (SD)] in obesity classes 1, 2, and 3 were −19 (2.9), −18.9 (2.9), −18.7 (2.9) & −24.2 (5.2), −23.8 (6.2), −24.5 (5.9), respectively. In the control group LV-GLS and RV-FWS values [mean (SD)] were −20.1 (3.0) & −27 (5.6), respectively. CH was associated with the greatest decrease in LV-GLS and RV-FWS in males and females, regardless of BMI (Figure 2). LV-GLS values [mean (SD)] associated to CH for obesity class 1, 2, and 3, and controls in females were −18.4 (3.4), −18 (3.1) −17.6 (3.6), and −17.8 (4), respectively, and for obesity class 1, 2, and 3, and controls in males were −16.1 (3.5), 16.5 (3.2), −14.4 (2.7), and −16.6 (4.7), respectively (Figure 1). Conclusion: Obesity associated to CVRF and CH have the lowest values of GLS in patients with normal ejection fraction. These values were exceedingly below average compared to other groups. These parameters should be used as reference values for this population. Funding Acknowledgement: Type of funding sources: None.